2021
DOI: 10.1038/s41396-021-01059-w
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface carbohydrates of symbiotic dinoflagellates and their role in the establishment of cnidarian–dinoflagellate symbiosis

Abstract: Symbiodiniaceae algae are often photosymbionts of reef-building corals. The establishment of their symbiosis resembles a microbial infection where eukaryotic pattern recognition receptors (e.g. lectins) are thought to recognize a specific range of taxon-specific microbial-associated molecular patterns (e.g. glycans). The present study used the sea anemone, Exaiptasia diaphana and three species of Symbiodiniaceae (the homologous Breviolum minutum, the heterologous-compatible Cladocopium goreaui and the heterolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 42 publications
(81 reference statements)
1
33
0
1
Order By: Relevance
“…High-mannoside glycans are the most abundant type of N-glycan in B. minutum , but increasing the abundance of high-mannoside glycans with inhibitors for glycan maturation pathways can decrease the colonization capacity of B. minutum ( 12 ). Similarly, Tortorelli et al ( 13 ) found higher abundances of high-mannoside glycans as measured by lectin array in nonnative species of algae, Cladocopium goreaui , and Fugacium kawagutii , compared to B. minutum , suggesting that an overabundance of high-mannoside glycans can inhibit symbiosis. The second-most abundant group of N-glycans in B. minutum are galactosylated glycans ( 12 ).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…High-mannoside glycans are the most abundant type of N-glycan in B. minutum , but increasing the abundance of high-mannoside glycans with inhibitors for glycan maturation pathways can decrease the colonization capacity of B. minutum ( 12 ). Similarly, Tortorelli et al ( 13 ) found higher abundances of high-mannoside glycans as measured by lectin array in nonnative species of algae, Cladocopium goreaui , and Fugacium kawagutii , compared to B. minutum , suggesting that an overabundance of high-mannoside glycans can inhibit symbiosis. The second-most abundant group of N-glycans in B. minutum are galactosylated glycans ( 12 ).…”
Section: Introductionmentioning
confidence: 89%
“…The second-most abundant group of N-glycans in B. minutum are galactosylated glycans ( 12 ). These glycans are less abundant in nonnative species of algae, Symbiodinium pilosum , C. goreaui , and F. kawagutii , as measured by lectin array compared to B. minutum ( 11 , 13 ). This supports the hypothesis that galactosylation is a marker for a compatible symbiont in Aiptasia ( 11 , 13 ).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations